LEGAL ANALYSIS OF THE LEASE AGREEMENT FOR ELECTRIC POWER PLANTS - Fraistifina; Kamelia; Hakim, Elsan Octavia; Andryawan (Awang Long Law Review, 2024)
Leasing consists of two types, namely finance lease with an option right and operating lease without an option right. A finance lease refers to an action by a financing company in carrying out financing activities by providing capital goods to the debtor, which will subsequently be utilized by the debtor for a specific period as agreed upon in the contract. Meanwhile, an operating lease is a type of lease that does not result in a substantial transfer of economic benefits or risks associated with the leased asset to the lessee. Generally, leasing in the electricity sector adopts the finance lease scheme due to the minimal risks posed to both parties. The issue the author seeks to examine pertains to the implementation, regulation, and accountability of leasing activities in the electricity sector. The type of research employed is normative legal research. The term 'juridical' refers to an approach based on applicable laws and regulations, while 'normative' refers to an approach conducted through primary legal materials. Normative juridical research utilizes primary legal sources as well as legal literature. Any party intending to lease electrical power must submit an application to PT PLN (Persero) in accordance with the provisions of the Decree of the Minister of Finance Number 1169/KMK.01/1991 concerning Leasing Activities. A juridical analysis of lease agreements for power plants is essential. This analysis seeks to identify potential legal issues that may arise and provide recommendations for improvements and enhancements in the execution of such lease agreements, thereby supporting the development of a sustainable and efficient electricity sector in Indonesia.